Marine‐terminating glaciers sustain high productivity in Greenland fjords. (4th August 2017) - Meire, Lorenz; Mortensen, John; Meire, Patrick; Juul‐Pedersen, Thomas; Sejr, Mikael K.; Rysgaard, Søren; Nygaard, Rasmus; Huybrechts, Philippe; Meysman, Filip J. R.
Abstract: Accelerated mass loss from the Greenland ice sheet leads to glacier retreat and an increasing input of glacial meltwater to the fjords and coastal waters around Greenland. These high latitude ecosystems are highly productive and sustain important fisheries, yet it remains uncertain how they will respond to future changes in the Arctic cryosphere. Here we show that marine‐terminating glaciers play a crucial role in sustaining high productivity of the fjord ecosystems. Hydrographic and biogeochemical data from two fjord systems adjacent to the Greenland ice sheet, suggest that marine ecosystem productivity is very differently regulated in fjords influenced by either land‐terminating or marine‐terminating glaciers. Rising subsurface meltwater plumes originating from marine‐terminating glaciers entrain large volumes of ambient deep water to the surface. The resulting upwelling of nutrient‐rich deep water sustains a high phytoplankton productivity throughout summer in the fjord with marine‐terminating glaciers. In contrast, the fjord with only land‐terminating glaciers lack this upwelling mechanism, and is characterized by lower productivity. Data on commercial halibut landings support that coastal regions influenced by large marine‐terminating glaciers have substantially higher marine productivity. These results suggest that a switch from marine‐terminating to land‐terminating glaciers can substantially alter the productivity in the coastal zone around Greenland with potentially large ecological and socio‐economic implications. Abstract : Marine productivity is very differently regulated in fjords influenced by land‐terminating or marine‐terminating glaciers. Fjords with marine‐terminating glaciers sustain a much higher productivity due to nutrient upwelling by rising subsurface meltwater. Glacier retreat hence can have large impact on marine productivity and fisheries in the fjords around Greenland.